Sergei Bulgakov’s sophiology of death - Kiejzik, Lilianna ca. 20./21. Jh. (Studies in East European thought, 2010)
In this paper I present Bulgakov’s conception of the sophiology of death considered, first, as a science of God’s Wisdom and, second, as the content of Bulgakov’s work entitled “Sophiology of Death.”